2019
DOI: 10.7554/elife.49501
|View full text |Cite
|
Sign up to set email alerts
|

Single cell analysis reveals immune cell–adipocyte crosstalk regulating the transcription of thermogenic adipocytes

Abstract: Immune cells are vital constituents of the adipose microenvironment that influence both local and systemic lipid metabolism. Mice lacking IL10 have enhanced thermogenesis, but the roles of specific cell types in the metabolic response to IL10 remain to be defined. We demonstrate here that selective loss of IL10 receptor α in adipocytes recapitulates the beneficial effects of global IL10 deletion, and that local crosstalk between IL10-producing immune cells and adipocytes is a determinant of thermogenesis and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 52 publications
4
108
2
Order By: Relevance
“…Expansion of brown adipose tissue (BAT) and increased appearance of beige adipocytes in inguinal white adipose tissue (iWAT) of mice and humans during cold exposure is associated with remodeling of tissue architecture [8][9][10] , and is controlled by activation of local sympathetic nerve fiber (SNF) activity [11][12][13][14] . Single cell RNA transcriptomic analysis has corroborated the extensive cellular heterogeneity of adipose depots and identified various resident immune cells and other cell types that are present [15][16][17][18][19][20] . Moreover, the association between increased abundance of iWAT macrophages with anti-inflammatory, alternatively activated properties and cold-induced adipose remodeling has been demonstrated 15,[21][22][23] .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Expansion of brown adipose tissue (BAT) and increased appearance of beige adipocytes in inguinal white adipose tissue (iWAT) of mice and humans during cold exposure is associated with remodeling of tissue architecture [8][9][10] , and is controlled by activation of local sympathetic nerve fiber (SNF) activity [11][12][13][14] . Single cell RNA transcriptomic analysis has corroborated the extensive cellular heterogeneity of adipose depots and identified various resident immune cells and other cell types that are present [15][16][17][18][19][20] . Moreover, the association between increased abundance of iWAT macrophages with anti-inflammatory, alternatively activated properties and cold-induced adipose remodeling has been demonstrated 15,[21][22][23] .…”
Section: Introductionmentioning
confidence: 94%
“…2) and cell autonomous effects also appear not to play a major role 34 , we hypothesized that other adipose resident cell types may be targets of FASN-deficient adipocyte signals. We therefore applied single cell RNA-seq, a powerful technique to identify cell types and their mRNA expression profiles within complex tissues including adipose tissues from cold exposed mice 15,19,20,50 , to this question. The stromal vascular fractions (SVF) of iWAT from control and iAdFASNKO mice were isolated and subjected to RNA-seq analysis (see single cell RNA-seq workflow for more details related to the protocol in Extended Data Fig.…”
Section: Nrg4 Deficiency Attenuates Cold-induced But Not Iadfasnko-inmentioning
confidence: 99%
“…WAT heterogeneity in mice has recently been revealed by scRNA-seq (Burl et al, 2018;Hepler et al, 2018;Schwalie et al, 2018;Cho et al, 2019;Merrick et al, 2019;Rajbhandari et al, 2019). We then profiled the expression of newly-identified white adipocyte progenitor marker genes (Rondini and Granneman, 2020) in human BAT stromal cells.…”
Section: Identification Of Conserved Markers For Brown Adipose Progenmentioning
confidence: 99%
“…Within the adipose tissue, adipocyte stem/progenitor cells and committed preadipocytes reside in the stromal vascular fraction (SVF) and normally express lineage-negative markers including PDGFRα, DLK1, CD34, SCA1, CD29, and CD24 (Rodeheffer et al, 2008;Schulz et al, 2011;Berry and Rodeheffer, 2013). Profiling of the SVF cells from WAT depots at the single-cell level has revealed a developmental hierarchy of white adipocyte precursors (Burl et al, 2018;Hepler et al, 2018;Schwalie et al, 2018;Cho et al, 2019;Merrick et al, 2019;Rajbhandari et al, 2019). However, the cellular heterogeneity and differentiation trajectory of brown adipose precursors have not been defined yet.…”
Section: Introductionmentioning
confidence: 99%
“…68They arise from specific precursor cells, distinct from white adipocytes (Shinoda et al, 2015; Wu et al, 69 2012; Xue et al, 2015), but more recent data demonstrated a continuum in the expression 70 pattern (Altshuler-Keylin et al, 2016;Shao et al, 2019). Additional studies identified four distinct 71 human adipocyte subtypes differentially associated with thermogenesis and/or lipid storage (Min et al, 72 2019), and a recent study demonstrated the presence of brown adipocytes in mice with different 73 thermogenic activities in vivo , while another report showed immune cells and 74 adipocyte interaction via Il-10 using single-nucleus RNA-Seq (snRNA-seq) (Rajbhandari et al, 2019). 75…”
mentioning
confidence: 99%